An Amazing Series

Algebra Level 2

S = 1 + 2 + 3 + + ( n 1 ) + n + ( n 1 ) + + 3 + 2 + 1 S=1+2+3+\cdots+(n-1)+n+(n-1)+\ldots+3+2+1

Find general formula of S S .

n 2 {n}^{2} 2 n 2 2{n}^{2} ( n 2 ) 2 {\left(\dfrac{n}{2}\right)}^{2} 2 n 2n

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Michael Fuller
Dec 19, 2015

= ~~~~~\huge =~~

I like visual thinking

Denis Herda - 5 years, 5 months ago
Akshat Sharda
Dec 18, 2015

S = 1 + 2 + 3 + . . . + ( n 1 ) + n + ( n 1 ) + . . . + 3 + 2 + 1 = n ( n + 1 ) n = n 2 + = n 2 \begin{aligned} S & = 1+2+3+...+(n-1)+n+(n-1)+...+3+2+1 \\ & = \not{2} \cdot \frac{n(n+1)}{\not{2}}-n= n^2+\not{n}-\not{n} \\ & = \boxed{n^2} \end{aligned}

Rishabh Jain
Dec 20, 2015

S=2(1+2+3...+n)-n =2(n/2(2+n-1))-n =n^2

Ashish Menon
Jun 21, 2016

It reduces to 2 × n ( n + 1 ) 2 n = n 2 + n n = n 2 2 × \dfrac{n(n + 1)}{2} - n = n^2 + n - n = \color{#3D99F6}{\boxed{n^2}} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...